Blue Large-Amplitude Pulsators (BLAPs): possible origin, evolutionary status, and nature of their pulsations - Corsico, Alejandro Hugo (2018)
The Blue Large-Amplitude Pulsators (BLAPs) constitute a new class ofpulsating stars. They are hot stars with effective temperatures of Teff∼30000 K and surface gravities of logg∼4.9, that pulsatewith periods in the range ∼20−40 min. In Romero et al. (2018), weproposed that BLAPs are hot low-mass He-core pre-white dwarf (WD) stars thatpulsate either in high-order non-radial g(gravity) modes or low-order radialmodes, including the fundamental radial mode. The theoretical modes withperiods in the observed range are unstable due to the κ mechanismassociated with the Z bump in the opacity at logT∼5.25. In thiswork, we extend the study of Romero et al. (2018) by assessing the rate ofperiod changes of nonradial g modes and radial modes and comparing them withthe values measured for BLAPs, in an attempt to validate the proposedevolutionary scenario, and to discern whether the observed modes are high-orderg modes or radial modes.